The Potential of Municipal Sukuk Issuance in Indonesia - A Review of Theoretical Research: Potensi Penerbitan Sukuk Daerah di Indonesia - Tinjauan Penelitian Teoritis - Ulfah, Indar Fauziah (Perisai : Islamic Banking and Finance Journal, 2023)
The main objective of this study is to provide local authorities with municipal Sukuk as an alternative to financing local infrastructure and developing areas. This study reviews the previous literature examining contemporary municipal sukuk and Discussed issues related to restrictions on the issuance of municipal sukuk. The research shows that the barriers to municipal Sukuk issuance are: Regional Barriers, Credit risk, Political Risk, Credit Weakness among stakeholders, Lack of through understanding of Shariah and financing and implementation. It was an exploratory study and aimed to identify barriers to becoming municipal bonds. Blocks of municipal Sukuk are listed from all possible sources. The study proposes some practical ways to overcome the obstacles to the provision of municipal sukuk in order to promote more municipal sukuk in various regions of the country to support sustainable development through equitable infrastructure distribution.